2019
DOI: 10.3892/mco.2019.1967
|View full text |Cite
|
Sign up to set email alerts
|

Alarming endoscopic data in young and older asymptomatic people: Results of an open access, unlimited age colonoscopic screening for colorectal cancer

Abstract: There is a lack of a national organized screening program for colorectal cancer in Greece, and asymptomatic detection is usually the result of individual decisions. The collection of epidemiologic endoscopic data from a population of interest would therefore provide valuable information for future treatment guidance, especially during periods of economic austerity. The current cross-sectional study included 380 asymptomatic, average risk individuals undergoing screening colonoscopy for the first time, during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Meta-analysis was performed on additional age categories delineated as younger than 40 years, 37,45,48 40-44 years 37,40,43,45,48 and 45-49 years. [38][39][40]43,45,[47][48][49] Neoplasia outcomes were significantly different by age groups (c 2 ¼ 13.038; P ¼ .001). Pooled rates of EAO-CRN increased from 8.1% (95% CI, 0.050%-0.127%) to 11.7% (95% CI, 0.092%-0.149%) to 17.8% (95% CI, 0.145%-0.216%) for ages younger than 40 years, 40-44 years, and 45-49 years, respectively (Figure 3A).…”
Section: Yield Of Colonoscopy By Age Groupsmentioning
confidence: 97%
See 3 more Smart Citations
“…Meta-analysis was performed on additional age categories delineated as younger than 40 years, 37,45,48 40-44 years 37,40,43,45,48 and 45-49 years. [38][39][40]43,45,[47][48][49] Neoplasia outcomes were significantly different by age groups (c 2 ¼ 13.038; P ¼ .001). Pooled rates of EAO-CRN increased from 8.1% (95% CI, 0.050%-0.127%) to 11.7% (95% CI, 0.092%-0.149%) to 17.8% (95% CI, 0.145%-0.216%) for ages younger than 40 years, 40-44 years, and 45-49 years, respectively (Figure 3A).…”
Section: Yield Of Colonoscopy By Age Groupsmentioning
confidence: 97%
“…The most common reason for excluding full-text articles was that higher-than-averagerisk individuals were included in the study, such as those with a family history of CRC or symptoms prompting the colonoscopy examination. There were 17 total articles included with 51,811 individuals younger than 50 years [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] (Figure 1, Supplementary Table 2). Seven studies were from East Asia (4 from South Korea, 2 from Taiwan, and 1 from China), 5 from the United States, 3 from Europe (Romania, Germany, and Greece), and 2 from the Middle East (Israel and Iran).…”
Section: Search Strategy and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with available data for individuals ages 45 to 49 reported nonadvanced adenoma rates ranging from 8.2% to 20.2% and advanced adenoma rates of 1.2% to 12.5%. [42][43][44][45] Kolb et al 46 conducted a systematic review and meta-analysis of screening colonoscopy performed in 51,811 average-risk individuals under age 50 from 17 international studies published from 2002 to 2020, 5 of which were performed in the United States. Among those ages 45 to 49, this systematic review and meta-analysis reported a pooled rate of any colorectal neoplasia of 17.8% (95% CI, 14.5-21.6) and advanced colorectal neoplasia of 3.6% (95% CI, 1.9-6.7).…”
Section: Colonoscopy Screeningmentioning
confidence: 99%